Latin poetry and the idea of Rome in the Greek novel - Jolowicz, D (2015)
My doctoral project focuses on texts known as the 'ancient Greek novels'. I am interested in how the novels—and imperial Greek literature more generally—interact with Latin literature and Roman power. The major claim of the thesis is that the Greek novelists Chariton, Xenophon of Ephesus, Achilles Tatius, and Longus (writing under the Roman Empire in the first three centuries CE) are engaging meaningfully with literature written in Latin, especially Augustan poetry of the first century BCE. The claim has never been systematically explored, and runs counter to received wisdom. The thesis demonstrates that the novelists are invested in Latin literature (especially Vergil and the elegists) and Roman cultural narratives, and potentially lays the groundwork for a major overhaul and re-evaluation of the way we read imperial Greek literature. It draws two major conclusions: (i) that the Greek novels are deeply invested in Latin literature and Roman cultural narratives at the level of poetics, and (ii) that this literary engagement is part of a more subterranean political agenda through which the texts articulate a resistance to Rome and empire. Chapter 1 explores the novelists' literary and ideological appropriation of the elegiac metaphors of seruitium and militia amoris. Chapter 2 analyses Chariton’s engagement with the Aeneid. Chapter 3 pursues Chariton’s relationship with Ovid’s epistolary and exilic poetry, as well as with Latin elegy more generally. Chapter 4 examines Achilles’ use of Latin elegy as part of his redefinition of the novelistic genre. Chapter 5 explores how Achilles mediates his version of Roman foundation narratives such as Romulus’ Asylum, and the rapes of the Sabine women, Lucretia, and Verginia. Chapter 6 examines the gamut of Longus’ responses to Latin literature and Roman culture, including Vergil, Ovid, the Lupercalia, and Romulus and Remus. The Appendices tabulate undiscussed allusions.